2012 IEEE 24th International Conference on Tools With Artificial Intelligence 2012
DOI: 10.1109/ictai.2012.72
|View full text |Cite
|
Sign up to set email alerts
|

Determining Redundant Actions in Sequential Plans

Abstract: Abstract-Automated planning even in its simplest form, classical planning, is a computationally hard problem. With the increasing involvement of intelligent systems in everyday life there is a need for more and more advanced planning techniques able to solve planning problems in little (or real) time. However, planners designed to solve planning problems as fast as possible often provide solution plans of low quality. The quality of solution plans can be improved by their post-planning analysis by which redund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Clearly, this is because of the IAE method is specific, i.e., only pairs or nested pairs of inverse actions are considered. Surprisingly, the runtime is high despite the complexity results (Chrpa, McCluskey, and Osborne 2012a). This can be partially explained by the fact, that IAE takes input in the PDDL format, which is much more complex to process than the SAS+ format.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Clearly, this is because of the IAE method is specific, i.e., only pairs or nested pairs of inverse actions are considered. Surprisingly, the runtime is high despite the complexity results (Chrpa, McCluskey, and Osborne 2012a). This can be partially explained by the fact, that IAE takes input in the PDDL format, which is much more complex to process than the SAS+ format.…”
Section: Resultsmentioning
confidence: 97%
“…Both Perfect Justification and Minimal reduction are NP-complete. Determining redundant pairs of inverse actions (inverse actions are those that revert each other's effects), which aims to eliminate the most common type of redundant actions in plans, has been also recently studied (Chrpa, McCluskey, and Osborne 2012a;2012b).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Chrpa, McCluskey, and Osborne (2012b) proposed a technique for identifying redundant pairs of inverse actions. Later the technique was extended to consider "nested" pairs inverse actions (Chrpa, McCluskey, and Osborne 2012a). Balyo, Chrpa, and Kilani (2014) addressed the problem of finding a minimal reduction (proven to be NP-complete (Nakhost and Müller 2010b)) by compiling it to MaxSAT and have empirically shown that (G)AE often find minimal reductions.…”
Section: Related Workmentioning
confidence: 99%
“…A specific form of action reversibility involving the search for an inverse action has been investigated (Koehler and Hoffmann 2000;Chrpa, McCluskey, and Osborne 2012). The existence of a pair of inverse actions is a special case of action reversibility, where the reverse plan contains only one action.…”
Section: Introductionmentioning
confidence: 99%